Investigation Of The Anti-Proliferative Effect Of Synthetic 1-[(Bromomethyl)(phenyl) methyl]-2-(2,4dinitrophenyl)hydrazine Derivative On Cervical Cancer Cells - Othuman, Faiqah Husna Shaik (2016)
Cervical cancer remains as the second most common type of cancer in women and it is the third leading cause of death despite various treatments that are available. Inefficiency of present treatments had triggered scientists to seek for an alternative treatment for this disease. Development of new anti-proliferative agent for cervical cancer is an important innovation in fighting this miserable disease. Although, synthetic hydrazone derivatives are widely being used in cancer research, the actual anticancer mechanism shown by these chemicals is still not yet understood.